PERAN TATA KELOLA PERUSAHAAN DALAM PROFITABILITAS, STRUKTUR MODAL, DAN PENGHINDARAN PAJAK TERHADAP NILAI PERUSAHAAN - Indawati; Ngadiman; Yustina Peniyanti Jap (Fakultas Ekonomi Universitas Tarumanagara, 2023)
This research aims to determine how the effect of profitability, capital structure and tax avoidance on firm value and to find out how the role of corporate governance in moderating the effect of profitability, capital structure and tax avoidance on firm value in manufacturing companies in the non-cyclical consumer goods industry sector listed on the Indonesian Stock Exchange (IDX) for the period 2017 to 2020. The sample was selected using the purposive sampling method and the valid data were 34 companies. Based on the background, previous research and the underlying theory, the hypothesis of this research is that profitability and capital structure have a positive effect on firm value, tax avoidance has a negative effect on firm value, and corporate governance can moderate the effect of profitability, capital structure and tax avoidance on firm value. The data analysis technique is multiple linear regression with moderator regression analysis (MRA). The results of this research show that: (1) Profitability has a positive effect on firm value (2) Capital structure does not have a positive effect on firm value, (3) Tax avoidance does not negatively affect firm value, (4) Corporate Governance does not moderate the influence of profitability, structure capital with equity liability ratio (DER) indicators and tax avoidance on firm value, (5) Good Corporate Governance is proven to moderate the effect of capital structure with asset liability ratio (DAR) indicators on firm value. The implication of this research is the need to increase the role of corporate governance and improve corporate governance mechanisms in Indonesia to increase the value of the company which will provide a good signal for investors.